2019
DOI: 10.1002/jat.3788
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐specific immune‐modulation of cadmium on murine macrophages and mast cell lines in vitro

Abstract: Toxic trace metals are widespread contaminants that are potentially immunotoxic even at environmentally low exposure levels. They can modulate the immunity to infections, e.g., in wildlife species living in contaminated areas. The diverse immune cell types can be differentially affected by the exposure leading to the modulation of specific protective mechanisms. Macrophages and mast cells, part of the innate immune system, trigger immune responses and perform particular effector functions. The present study co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 81 publications
0
12
0
Order By: Relevance
“…However, contrasting effects of lead on nitric oxide production have been reported without clearly recognized mechanisms (Tian and Lawrence 1995; Sharifi et al 2005). Induction of nitric oxide was also noted in the cadmium (Cd) 2+ ‐exposed mouse macrophage RAW264.7 cell line at noncytotoxic concentrations, which was also associated with a depletion of GSH (Garcia‐Mendoza et al 2019). Both Cd 2+ and Pb 2+ are nonredox active divalent metals (Matovic et al 2015) with a high affinity to sulfhydryl (–SH) groups and are known to share similar modes of action with respect to the redox status of cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, contrasting effects of lead on nitric oxide production have been reported without clearly recognized mechanisms (Tian and Lawrence 1995; Sharifi et al 2005). Induction of nitric oxide was also noted in the cadmium (Cd) 2+ ‐exposed mouse macrophage RAW264.7 cell line at noncytotoxic concentrations, which was also associated with a depletion of GSH (Garcia‐Mendoza et al 2019). Both Cd 2+ and Pb 2+ are nonredox active divalent metals (Matovic et al 2015) with a high affinity to sulfhydryl (–SH) groups and are known to share similar modes of action with respect to the redox status of cells.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, mast cell lipopolysaccharide-induced tumour necrosis factor-alpha and IgE-mediated histamine release were reduced by cadmium. These data indicate potentially differential effects of cadmium among murine innate immune cell types, where mast cells would be more susceptible to oxidative stress and their function might be at a higher risk to be modulated compared to macrophages.” [ 153 ]…”
Section: Commonality Of Contributing Factors Between Ibd and Id - Detailsmentioning
confidence: 99%
“…reported that under Cd exposure in vitro , mouse mast cells showed full dose-response depletion of glutathione (GSH) to below cytotoxic levels. In contrast, LPS-induced TNF-α and immunoglobulin (Ig)E-mediated histamine release in mast cells were attenuated by Cd ( 65 ) ( Figure 2 ). Therefore, under Cd exposure, mast cells are more sensitive to oxidative stress.…”
Section: Regulatory Effects Of CD On Innate Immunitymentioning
confidence: 99%
“…Mast cells are distributed throughout the body, generally participate in humoral and antibody-mediated immune responses, and play an important role in the first line of immunity (90). Cd toxicity modes, such as oxidative stress, depletion of antioxidants, and induction of apoptosis, have different outcomes, depending on the sensitivity of each cell type to different mechanisms (65). Garcıá-Mendoza et al reported that under Cd exposure in vitro, mouse mast cells showed full dose-response depletion of glutathione (GSH) to below cytotoxic levels.…”
Section: And Mast Cellsmentioning
confidence: 99%